Paternal aging impacts expression and epigenetic markers as early as the first embryonic tissue lineage differentiation - Michelle M. Denomme; Blair R. McCallie; Mary E. Haywood; Jason C. Parks; William B. Schoolcraft; Mandy G. Katz-Jaffe (Human Genomics, 2024)
Abstract Background Advanced paternal age (APA) is associated with adverse outcomes to offspring health, including increased risk for neurodevelopmental disorders. The aim of this study was to investigate the methylome and transcriptome of the first two early embryonic tissue lineages, the inner cell mass (ICM) and the trophectoderm (TE), from human blastocysts in association with paternal age and disease risk. High quality human blastocysts were donated with patient consent from donor oocyte IVF cycles from either APA (≥ 50 years) or young fathers. Blastocysts were mechanically separated into ICM and TE lineage samples for both methylome and transcriptome analyses. Results Significant differential methylation and transcription was observed concurrently in ICM and TE lineages of APA-derived blastocysts compared to those from young fathers. The methylome revealed significant enrichment for neuronal signaling pathways, as well as an association with neurodevelopmental disorders and imprinted genes, largely overlapping within both the ICM and TE lineages. Significant enrichment of neurodevelopmental signaling pathways was also observed for differentially expressed genes, but only in the ICM. In stark contrast, no significant signaling pathways or gene ontology terms were identified in the trophectoderm. Despite normal semen parameters in aged fathers, these significant molecular alterations can adversely contribute to downstream impacts on offspring health, in particular neurodevelopmental disorders like autism spectrum disorder and schizophrenia. Conclusions An increased risk for neurodevelopmental disorders is well described in children conceived by aged fathers. Using blastocysts derived from donor oocyte IVF cycles to strategically control for maternal age, our data reveals evidence of methylation dysregulation in both tissue lineages, as well as transcription dysregulation in neurodevelopmental signaling pathways associated with APA fathers. This data also reveals that embryos derived from APA fathers do not appear to be compromised for initial implantation potential with no significant pathway signaling disruption in trophectoderm transcription. Collectively, our work provides insights into the complex molecular mechanisms that occur upon paternal aging during the first lineage differentiation in the preimplantation embryo. Early expression and epigenetic markers of APA-derived preimplantation embryos highlight the susceptibility of the future fetus to adverse health outcomes.